Mid-holocene variability of the East Asian monsoon based on bulk organic δ13C and C/N records from the Pearl River estuary, southern China - Yu, Fengling (2013)
Understanding the mid-Holocene dynamics of the East Asian monsoon (EAM) is integral to improving models of the Holocene development of the global climate system. Here we reconstruct the mid-Holocene EAM history from the Pearl River estuary, southern China, using bulk organic carbon isotopes (δ13C), total carbon to total nitrogen (C/N) ratios and total organic carbon (TOC) concentration. Sedimentary δ13C, C/N and TOC are potentially good indicators of changes in monsoonal precipitation strength. Sediments buried during a period of high precipitation exhibit a high proportion of terrigenous material, and have low δ13C and high C/N, and vice versa during a period of low precipitation. Results suggest a general decreasing trend in monsoonal precipitation from 6650 to 2150 cal. yr BP because of the weakening Northern Hemisphere insolation most likely related to the current precession circle. Superimposed on this trend are apparent dry–wet oscillations at centennial to millennial timescales most likely in response to solar activity. Mismatches between our δ13C record and results from the Dongge Cave in southern China at millennial timescales may indicate that the δ13C from the Pearl River estuary reveals changes in precipitation over a broader area than the δ18O from Dongge Cave.